온주밀감에서 유엽과와 직과의 생장과 당산 특성 - 김샛별(Sat-Byul Kim); 오은의(Eun Ui Oh); 박재현(Jae Hyun Park); 윤수현(Su-Hyun Yun); 오현우(Hyun Woo Oh); 강종훈(Jong Hoon Kang); 고상욱(Sang Wook Koh); 오현정(Hyun Jeong Oh); 송관정(Kwan Jeong Song) (Weon'ye gwahag gi'sulji, 2012)
The study was conducted to investigate the effect of fruit bearing type with leafy (LY) and leafless (LS) fruits on fruit growth, sugar, and acid characteristics in satsuma mandarin. Fruit growth including fruit length, diameter, shape index (diameter/length), weight, and size distribution was not different between LY and LS fruits at ripening time. Total soluble solids (TSS) concentration of the fruit juice increased and acidity decreased continuously and then TSS:acidity ratio increased with fruit development from 100 days after anthesis to ripening time. Soluble sugar was continuously increased, whereas organic acid decreased. Theses tendencies were related to the increase of sucrose and decline of citric acid, respectively. However, there was no effect of fruit bearing type on TSS, acidity, and TSS:acidity ratio, and soluble sugar and organic acid composition in fruit juice. Also, photosynthetic rate and chlorophyll index with SPAD value were not different between leaves adjacent to LY and LS fruits. The results indicated that fruit growth and sugar and acid characteristics were not affected by fruit bearing type with leafy and leafless fruits in satsuma mandarin. 본 연구는 온주밀감에서 유엽과와 직과의 착과 형태에 따른 과실의 생장과 당산 특성을 구명코자 수행하였다. 과실의 종경, 횡경, 과형지수(횡경/종경), 과중 및 크기 분포를 포함하는 수확기 과실의 생장에 있어서 유엽과와 직과에 따른 차이는 없었다. 만개 후 100일부터 수확기까지 과실 발육과 더불어 지속적으로 과즙의 총가용성고형물의 농도는 증가하고 산도는 감소하여 당산비는 증가하였다. 유리당은 지속적으로 증가한 반면 유기산은 감소하였다. 이들 경향은 각각 자당의 증가와 구연산의 감소와 관계되었다. 그러나 착과 형태가 과즙의 총가용성고형물, 산도, 당산비, 유리당 및 유기산 조성에 미치는 영향은 나타나지 않았다. 또한 유엽과와 직과에 가장 인접한 잎에서의 광합성율과 SPAD 값에 의한 엽록소 지수 간에도 차이가 없었다. 본 연구결과는 온주밀감에서 유엽과와 직과의 착과 형태에 따른 과실의 생장과 당산 특성에 차이가 없음을 나타내었다.